Descriptive study on the impact of COVID-19 on the level of depression, anxiety, and stress of midwives - 2021 - Rivera-Beltrán, Susana Elizabeth (2021)
Introduction: Health professionals are going through situations of uncertainty during the COVID-19 pandemic, expressing fear, anxiety, or stress, caused by drastic changes in daily and work life. In this context, the health of obstetricians was threatened by treating pregnant women with an added diagnosis of COVID-19 infection, placing them at risk of contagion, increasing even more in vulnerable obstetricians or with comorbidities, for which a significant number of obstetricians went to remote work. Even with limitations, obstetricians strive to meet institutional goals, however, they do not receive attention from their employers regarding their mental health, which should be given periodically, to keep them fit and continue working in this pandemic. Possibly this pandemic persists for a longer time, and through the application of the DASS-21 questionnaire, levels of depression, anxiety and stress are measured to detect cases and suggest their timely treatment. Objective: To measure the impact of COVID-19 on the level of depression, anxiety, and stress of Obstetricians during 2021. Materials and Methods: Non-experimental, descriptive, retrospective, cross-sectional design. Obstetricians from the SORISLO Obstetricians Union participated. Sample: 42 obstetricians (95% CI). Independent variable: Impact of COVID-19; dependent variable: level of depression, anxiety, stress. Technique: Survey. Instrument: DASS-21 questionnaire. Descriptive analysis, frequency distributions and percentages. Ethical principles: respect and non-maleficence towards obstetricians. Results: Obstetricians were found with mild depression 12%, moderate 2%, and severe 5%. Obstetricians with mild anxiety 12%, moderate 7%, severe 5%, and extremely severe 5%. Obstetricians with mild stress 10%, moderate 2%, and severe 2%. The highest prevalence of depression, anxiety, and stress occurred in adult obstetricians (30-59 years), with face-to-face tasks, and appointed servants. Conclusions: The COVID-19 pandemic has had a considerable impact on the level of depression, anxiety, and stress in obstetricians during 2021.